2021
DOI: 10.3390/su13169435
|View full text |Cite
|
Sign up to set email alerts
|

A Global Media Analysis of the Impact of the COVID-19 Pandemic on Chicken Meat Food Systems: Key Vulnerabilities and Opportunities for Building Resilience

Abstract: Food systems are increasingly under threat, with climate, biological, economic or policy shocks and stressors occurring at an increasing frequency and scale. Their complex and fragile nature has become even more apparent during the COVID-19 pandemic. A systematic review of news articles published globally between December 2019 and April 2020 was conducted to describe the impacts of the COVID-19 pandemic on the chicken meat system and to identify key vulnerabilities and intervention points to build resilience. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In Iran, pandemic-related rumors were also reported to have had an impact on the demand for poultry meat, with stakeholders' activities also being affected by import restrictions on raw materials due to the increase in border controls, rising prices of input materials, and supply restrictions on foreign currency [24]. In line with our study, a global media analysis concluded that COVID-19 mitigation measures, including lockdowns and movement restrictions, disrupted the PDN more than the SARS-CoV-2 virus itself [25]. The poultry market in countries like Bangladesh, Morocco, Nigeria, China, and Myanmar also reported incurred losses due to COVID-19-associated lockdowns [26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 85%
“…In Iran, pandemic-related rumors were also reported to have had an impact on the demand for poultry meat, with stakeholders' activities also being affected by import restrictions on raw materials due to the increase in border controls, rising prices of input materials, and supply restrictions on foreign currency [24]. In line with our study, a global media analysis concluded that COVID-19 mitigation measures, including lockdowns and movement restrictions, disrupted the PDN more than the SARS-CoV-2 virus itself [25]. The poultry market in countries like Bangladesh, Morocco, Nigeria, China, and Myanmar also reported incurred losses due to COVID-19-associated lockdowns [26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 85%
“…The beef and sheep supply chains were able to adapt, more than chicken and pork, due to the flexible nature of beef and sheep farming and due to farmers being able to hold animals on-farm for a few extra weeks or months. The "just in time" system of chicken production is noted by Chapot et al [13] to remove redundancy and allows streamlining, but it has left itself vulnerable worldwide [13].…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in redirecting supplies from foodservice to retail was also noted in other countries as well [10][11][12]. Disruptions were also noted in other supply chains including chicken meat [13], turkey, pork, and eggs [11].…”
Section: Introductionmentioning
confidence: 88%
“…Poultry production has an essential contribution in terms of food security and nutrition, with a fast-growing market [ 14 ], mostly due to poultry meat and eggs being an affordable protein source [ 15 ]. A significant number of regulations have led to a decrease in the use of antimicrobial agents in food animal production [ 16 ]; however, A. baumannii is commonly found in poultry and their produce.…”
Section: Introductionmentioning
confidence: 99%